2018
DOI: 10.14221/ajte.2018v43n5.7
|View full text |Cite
|
Sign up to set email alerts
|

Building Critically Reflective Practice in Higher Education Students: Employing Auto-ethnography and Educational Connoisseurship in Assessment

Abstract: This study posed the question: Does using an educational connoisseurship framework applied to auto-ethnography assist in the development of reflective practice in teacher education? The design of authentic assessments that assist students in making meaningful links between theory and practice is a complex process. We created an assessment task that was directly linked to the lived experience of the students and specifically focused on their educational practice. Students were required to write an auto-ethnogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Deconstructing the reflective writing framework in this case helped to provide manageable steps for students to follow and scaffolded the writing task. Similar forms of support were discussed in the study by Southcott and Crawford (2018) where the students were provided with a similar framework to help them focus their thinking and present their writing in a structured way. Furthermore, the study by Gadbury-Amyot and Overman (2018) also describes support to help students structuring a reflective portfolio.…”
Section: Reflective Writing Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Deconstructing the reflective writing framework in this case helped to provide manageable steps for students to follow and scaffolded the writing task. Similar forms of support were discussed in the study by Southcott and Crawford (2018) where the students were provided with a similar framework to help them focus their thinking and present their writing in a structured way. Furthermore, the study by Gadbury-Amyot and Overman (2018) also describes support to help students structuring a reflective portfolio.…”
Section: Reflective Writing Frameworkmentioning
confidence: 99%
“…Participants, who were trainee music teachers, in the Southcott and Crawford (2018) qualitative study indicated that reflective writing via autoethnography was helpful overall to the experience of reflective writing for assessment, especially with understanding past experiences in order to lay stronger foundations for the future. The literature also suggests that a positive experience for students has been the conceptualisation of their discipline and to develop deeper learning relevant to upcoming real-world professional practice (Ono & Ichii, 2019) which can improve student confidence going forward into the real world of employment.…”
Section: Positive Experiencesmentioning
confidence: 99%
“…Some studies have supported the role of reflective journals in improving reflective thinking (Bruno & Dell'Aversana, 2017;Griggs et al, 2018). Still, some others have shown the effect of reflective practice on language learning (Fuertes-Camacho et al, 2021;Southcott & Crawford, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Reflexive practice is the process of intentionally examining one's practice at distinct times; in the middle of the practice, immediately after the practice has concluded, and some time afterward [27]- [29]. This process is especially effective within educational contexts, where the pacing can be relatively rapid, as there is always more content to cover and students to oversee.…”
Section: Effective Methods For Faculty Apprenticeship From Student Te...mentioning
confidence: 99%